2014
DOI: 10.20996/1819-6446-2014-10-2-153-159
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and Its Correlates in the Russian Population (Results of Esse-Rf Epidemiological Study)

Abstract: Сведения об авторах: Шальнова Светлана Анатольевна-д.м.н., профессор, руководитель отдела эпидемиологии хронических неинфекционных заболеваний Государственного научноисследовательского центра профилактической медицины Деев Александр Дмитриевич-к.ф.-м.н., руководитель лаборатории медицинской биостатистики того же центра Артамонова Галина Владимировна-д.м.н., профессор, зам. директора по научной работе Научно-исследовательского института комплексных проблем сердечно-сосудистых заболеваний Сибирского отделения РА… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
0
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 31 publications
2
0
0
4
Order By: Relevance
“…In our study, we observed frequent dyslipidemia: increased LDL >3.0 mmol/l was found in 62-67%, hypertriglyceridemia in 26-28%, and hyperuricemia in 39-49% of patients. This is consistent with epidemiological data on lipid and purine metabolism pathology for russian population: 59.7 ± 0.34% of the population had elevated LDL, 19.5 ± 0.28% had hypertriglyceridemia (18), and 16.8% had hyperuricemia (19). At the same time, hyperuricemia among our patients seems to be more than in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we observed frequent dyslipidemia: increased LDL >3.0 mmol/l was found in 62-67%, hypertriglyceridemia in 26-28%, and hyperuricemia in 39-49% of patients. This is consistent with epidemiological data on lipid and purine metabolism pathology for russian population: 59.7 ± 0.34% of the population had elevated LDL, 19.5 ± 0.28% had hypertriglyceridemia (18), and 16.8% had hyperuricemia (19). At the same time, hyperuricemia among our patients seems to be more than in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…According to the multicenter research project ESSE-RF in 2013-2014, hyperuricemia prevalence in Russia reached 16.8% (25.3% in men and 11.3% in women) [13]. The study confirmed a number of associations of hyperuricemia prevalence with gender, age, and some lifestyle characteristics.…”
Section: Introductionsupporting
confidence: 56%
“…Установлено, что у этнических корейцев наблюдаются более высокие значения МК по сравнению с европейцами, уровень МК которых соответствовал общероссийскому [22]. Указанный факт требует проведения более детального анализа связи между распространенностью гиперурикемии и риском развития ССЗ у лиц корейской этнической группы и диктует необходимость организации динамического мониторинга за выбранной группой обследованных.…”
Section: Discussionunclassified